2013
DOI: 10.1002/ep.11841
|View full text |Cite
|
Sign up to set email alerts
|

Evolution, detrimental effects, and removal of oxygen in microalga cultures: A review

Abstract: Large quantity of oxygen evolves as a byproduct of photosynthesis in microalga cultivation. As a result, dissolved oxygen of 100-400% air saturation or even higher is commonly observed in microalgal cultures. High concentration of dissolved oxygen may inhibit photosynthesis, cause photochemical damages to photosynthetic apparatus and other cellular components, result in reduction of cell growth or even culture collapse. Effective deoxygenation mechanisms are required to maintain dissolved oxygen at a level tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0
5

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(28 citation statements)
references
References 59 publications
1
22
0
5
Order By: Relevance
“…These values are comparable with horizontal tubular PBR, which was reported as from 3.6 to 10.8 h −1 (Peng et al 2013). However, with still the same rocking cycle of 1 s, k L a in 7.5 cm culture was only 1.04 h…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…These values are comparable with horizontal tubular PBR, which was reported as from 3.6 to 10.8 h −1 (Peng et al 2013). However, with still the same rocking cycle of 1 s, k L a in 7.5 cm culture was only 1.04 h…”
Section: Discussionsupporting
confidence: 88%
“…The problem for oxygen, however, is still to be studied, since it may cause photo-inhibition when accumulated to high level (Peng et al 2013). In this study, there was great variation on (Peng et al 2013).…”
Section: Discussionmentioning
confidence: 74%
“…Controlling contamination from biological agents such as microalga‐predator protozoa is a major contributor to the high costs of microalgal cultivation, especially for freshwater microalgae, as it demands intensive energy consumption for medium and system sterilization and requires costly closed systems and cautious procedures for maintaining sterility . Furthermore, deoxygenation, which is required for mitigation of oxygen stress to microalgal cells, is vastly more complicated and costly in the closed systems that are required for sterile cultivation of microalgae.…”
Section: Introductionmentioning
confidence: 99%
“…A significant problem arises during the operation of closed photobioreactors when the microalgal culture reaches toxic oxygen concentrations. Weissman et al (1988) reported toxic oxygen concentrations as high as 100 mg L −1 for a tubular photobioreactor, although Peng et al (2013) reported that inhibition depends on the microalgal strains or population, so oxygen concentrations could range from 8.0 to 53 mg L −1 . If an adequate control of the dissolved oxygen concentration is implemented (i.e., stripping out), it would avoid reaching toxic concentrations.…”
Section: Introductionmentioning
confidence: 96%